Local photo-oxidation of individual single walled carbon nanotubes probed by femtosecond four wave mixing imaging. Issue 1 (10th November 2014) - Aumanen, Jukka; Johansson, Andreas; Herranen, Olli; Myllyperkiö, Pasi; Pettersson, Mika
Abstract : Non-linear photo-oxidation of single walled carbon nanotubes (SWCNTs) is induced by femtosecond laser pulses and imaged by four wave mixing microscopy. Oxidation is localized on an individual SWCNT within optical resolution. Abstract : Photo-oxidation of individual, air-suspended single walled carbon nanotubes (SWCNTs) is studied by femtosecond laser spectroscopy and imaging. Individual SWCNTs are imaged by four wave mixing (FWM) microscopy under an inert gas (Ar or N2 ) atmosphere. When imaging is performed in an ambient air atmosphere, the decay of the FWM signal takes place. Electron microscopy shows that SWCNTs are not destroyed and the process is attributed to photoinduced oxidation reactions which proceed via a non-linear excitation mechanism, when irradiation is performed with ∼30 fs pulses in the visible spectral region (500–600 nm). Photo-oxidation can be localized in specific regions of SWCNTs within optical resolution (∼300 nm). The effect of photo-oxidation on Raman spectra was studied by irradiating a local spot on an individual SWCNT and comparing the spectra of irradiated and non-irradiated regions of the same tube. It is shown at an individual nanotube level that oxidation leads to a decrease of the intensity of the Raman signal and an upshift of the G-band.